Kemungkinan Penggunaan Pupuk Nitrofosfat di Indonesia. (Possibility of the Use of Nitrophosphate in Indonesia) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1981)
ABSTRAK Within the last nine years the fertilizer consumption in Indonesia increases rapidly at a yearly average rate of 14.2 %. Straight fertilizers still dominate at the amount of 88 % of the total consumption. The distribution among the crops are 48% for rice. 33% for the other food crops, and 19 % for the estate crops. Java, including Madura, uses 85.5 % by fertilizer weight. In terms of nutrient applied, this part of Indonesia consumes 87.8 % of the totally applied N, 78.7 % of P205, and 69,1 % of K20. Agricultural development in Indonesia is at the take off stage. This is assumed on the quite high yearly rate of increase in fertilizer consumption of 14.2 %. while the level of nutrient application per hectare is moderate at, an average of 35 Kg. At this stage the use of compound fertilizers need to be introduced to the farmers in order to improve the efficiency of application. This is especially important for Java and Madura where fertilization is most advanced. The compound fertilizer DAP is already accepted by farmers. although still at a modest scale of 4 - 5 % of the total consumption. Field trials have confirmed the advantage of DAP over the use of the single fertilizer Urea and TSP. Since the last four years DAP has been produced domestically. The question arises whether it will be proper to introduce another compound fertilizer, while the compatibility of DAP with the common farmer's practice needs still he established. It is recommended that nitrophosphate should go through the usual trials before it may he eventually released for common use. For this purpose the identification of priority areas is appriopriate, including the planning of the marketing channels. Key Words: konsumsi pupuk, K2O, takaran pupuk